2018
DOI: 10.1186/s13048-018-0432-x
|View full text |Cite
|
Sign up to set email alerts
|

Fresh versus frozen embryo transfer for full-term singleton birth: a retrospective cohort study

Abstract: BackgroundImprovements in vitrification and frozen embryo transfer (FET) technologies have rapidly increased, and some evidence suggests that FET may increase pregnancy rates and lead to more favourable perinatal outcomes. However, the outcome of interest should be offspring safety. Therefore, the primary objective of our study was to investigate whether FET was preferable to fresh embryo transfer (ET) in terms of full-term neonatal birthweight and congenital malformations.MethodsThis was a retrospective cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 40 publications
3
34
0
1
Order By: Relevance
“…Our ndings are consistent with the pre-existing meta-analysis [3,29] and retrospective studies [30,31] published until 2018 showing that singletons born after FET have higher birth weight and higher gestational age at birth but a higher risk of hypertensive disorders of pregnancy, while singletons born after fresh ET tend to have a higher risk of preterm birth and low birthweight. However, our single-center singleton study showed that compared to those born after fresh ET, singletons born after FET had higher birth weight but not increased LGA.…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings are consistent with the pre-existing meta-analysis [3,29] and retrospective studies [30,31] published until 2018 showing that singletons born after FET have higher birth weight and higher gestational age at birth but a higher risk of hypertensive disorders of pregnancy, while singletons born after fresh ET tend to have a higher risk of preterm birth and low birthweight. However, our single-center singleton study showed that compared to those born after fresh ET, singletons born after FET had higher birth weight but not increased LGA.…”
Section: Discussionsupporting
confidence: 92%
“…placenta previa, placental abruption, preterm delivery, low birth weight, perinatal mortality and SGA. Moreover, previously published studies have also reported that infant birth weights from FET cycles were higher than those of fresh embryo transfer cycles, with a crude mean difference of 126 g (65-205 g) calculated from their reports (Ishihara et al, 2014;Li et al, 2014;Pinborg et al, 2014;Ozgur et al, 2015;Korosec et al, 2016;Luke et al, 2017;Spijkers et al, 2017;Tsuji et al, 2017;Vidal et al, 2017;Zhang et al, 2018;Wei et al, 2019). In studies defining LGA according to the 90th percentile birth weight of a reference population, the LGA rates reported from FET cycles ranged between 13 and 23% (Korosec et al, 2016;Luke et al, 2017;Zhang et al, 2018;Wei et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that children born following FET have similar or in most areas even better perinatal outcome, as compared to children born after fresh ET (23,24). Moreover, while FET was shown to be associated with lower risk of prematurity and LBW in singletons, when compared with fresh ET, there is a growing concern that children born after FET have increased risk of LGA and/or macrosomia (25). Macrosomic/LGA births have a higher risk of fetal hypoxia, stillbirth, shoulder dystocia, cesarean section, postpartum hemorrhage, perineal lacerations and neonatal metabolic disorders at birth (26).…”
Section: Fet Pregnanciesmentioning
confidence: 99%